2018
DOI: 10.15639/teflinjournal.v29i1/129-148
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration Into Factors Associated With Reading Anxiety Among Taiwanese Efl Learners

Abstract: The present study was an elaboration on factors influencing for- eign language (FL) reading anxiety in EFL learners (n = 202) in Taiwan. Data were collected from three measures, a background information questionnaire, the Foreign Language Reading Anxiety Scale (FLRAS) and a semi-structured interview. The results showed that FL reading anxiety was associated with time spent on reading English, but not with gender and academic major. Moreover, FL reading anxiety was found to be positively correlated with text fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In her later study using a path analysis, Lien (2016) found that 372 Taiwanese college students' EFL reading anxiety had a negative effect on their metacognitive strategy use, with a few other variables such as self-perceived English proficiency and satisfaction over their proficiency. In addition, the study by Tsai and Lee (2018) also produced similar results with 202 Taiwanese university students responding to the FLRAS and the SORS. Using strategy use as a predictor variable, they found that students' employment of such strategies had a negative influence on reading anxiety.…”
Section: Reading Strategy Use and Reading Orientationsupporting
confidence: 55%
See 2 more Smart Citations
“…In her later study using a path analysis, Lien (2016) found that 372 Taiwanese college students' EFL reading anxiety had a negative effect on their metacognitive strategy use, with a few other variables such as self-perceived English proficiency and satisfaction over their proficiency. In addition, the study by Tsai and Lee (2018) also produced similar results with 202 Taiwanese university students responding to the FLRAS and the SORS. Using strategy use as a predictor variable, they found that students' employment of such strategies had a negative influence on reading anxiety.…”
Section: Reading Strategy Use and Reading Orientationsupporting
confidence: 55%
“…Language anxiety has been researched widely over four decades since the first leading studies (e.g., Chastain, 1975;Scovel, 1978) and related studies have offered information as to what individuals bring to the process of learning a target language and how they are involved in it. Compared to language learning anxiety, reading anxiety has only gained attention relatively recently and has been researched to examine its predictive power in reading performance and its impact on reading processes (Lien, 2011;Sellers, 2000;Shi & Liu, 2006;Tsai & Lee, 2018;Zhao et al, 2013). Sellers (2000) argues that successful reading, with the aim of adequate comprehension, requires a great deal of cognitive endeavors, such as orchestrating attention, memory, or problem-solving processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some scholars have found that male learners’ FLA is higher than that of female learners ( Lu and Liu, 2015 ), some believe that female learners’ FLA is higher than that of male learners ( Elkhafaifi, 2005 ), and some have pointed out that gender is not significantly correlated to FLA ( Shi and Fan, 2013 ). A few studies have found that the subject background of FLL is significantly correlated with FLA level: compared with FLL majoring in humanities, learners specializing in natural sciences have a higher level of FLA ( Wang T., 2014 ), while some researchers hold the opinion that there is no significant correlation between learners’ subject background and their FLA ( Tsai and Lee, 2018 ).…”
Section: Foreign Language Learners’ Negative Emotionsmentioning
confidence: 99%
“…In this regard, the teachers should provide opportunities to students to improve their speaking abilities in friendly atmospheres so that the students would feel relaxed to speak out loud as well as organize activities that truly promote the use of students' everyday conversation (Yamsri et al, 2020). The anxiety of making mistakes also affected the students' reading abilities (Al Farug, 2019;Tsai & Lee, 2018). For example, Al Farug (2019) found that the material features, namely unfamiliar words and culture along with the personal factors of making mistakes were the two significant causes of students' anxiety.…”
Section: What Are the Teachers' Perceptions Towards The Non-formal Ed...mentioning
confidence: 99%